PENDAMPINGAN MASYARAKAT DESA GEGER DALAM PENGELOLAAN SAMPAH DAN PENDIDIKAN KARAKTER BAGI SISWA SEKOLAH DASAR - Susi Ratnawati; Indah Safitri (Yayasan Pendidikan dan Kebudayaan Dharma Wacana, 2020)
Garbage in Indonesia is still a very troubling issue for the community. Lack of public awareness of the importance of being clean is still a problem. Likewise the importance of improving the quality of primary school education. Based on the description and problems above, the community service activities carried out are providing environmental education in waste management and improving the quality of primary school education through community service programs in Geger Village, Turi District, Lamongan Regency. Geger village was chosen as a place of community service because in this village there is still very little awareness of the community about the importance of maintaining cleanliness by not littering in rivers or rice fields. In the village of Geger there is also a lack of teaching staff for primary schools, so that there is often one teacher teaching for two classes, due to lack of teachers. In carrying out this service activity, there are two programs implemented, namely improving primary school education through soft skills and environmental education in waste management. Programs implemented include: educational programs in the form of school services, learning stimulations, character education, and synergy between parents, teachers, and students. For school service activities, in the form of physical activities by cleaning classrooms, cleaning windows, and grasses. Character education is done by shaping student behavior such as: polite behavior, as we do by shaking hands when going home from school, greeting the teacher when we meet, apologizing to the teacher or friend, saying thank you when receiving help and much more other positive things. In waste education, the program implemented: the separation between organic and non-organic waste, the making of a waste bank, the management of waste to produce organic fertilizer.